The Effect of Pre-Applied Titanium Dioxide Nanoparticles on Germination in Carthamus tinctorius L. Varieties - Gül, Volkan; Seckın Dınler, Burcu; Sefaoğlu, Fırat; Çetinkaya, Hatice; Koç, Fatma Nur (Journal of Agricultural Production, 2024)
In the present study, to promote sustainable nano-farming, the apparent effects of different concentrations (0, 100, 200, 300, 400, 500 ppm) of titanium dioxide nanoparticle (TiO2NPs) solutions on the germination percentage, index and duration of seeds belonging to Balcı, Dincer, Hasankendi, Koc, Olas, and Zirkon safflower varieties were investigated. Moreover, scanning electron microscopy (SEM) was employed to analyze TiO2NPs in germinated safflower varieties. Germination performance was TiO2NPs concentration and variety depended. It was determined that the seed samples displayed different responses to TiO2NPs concentrations; germination percentages were between 20.0±1.15 and 82.9±0.44%, germination durations were between 2.01±0.021 to 3.82±0.017 days, and germination indices were between 9.97±0.606 and 38.97±0.959. While the highest germination percentage (82.9±0.44%) was obtained from Dincer variety with 100 ppm TiO2NP pre-application, the lowest germination percentage (20.0±1.15% and 20.0±1.92%) was obtained from Balcı and Hasan Kendi varieties with 100 and 300 ppm TiO2NP pre-application. According to this result, although the highest germination percentage based on variety was obtained from the Dincer variety, the Balcı variety with the lowest germination percentage provided the most significant increase in the 200 ppm TiO2NPs application dose compared to the control. According to the germination percentage, it can be said that the most effective TiO2NPs application dose in Safflower varieties is 200 ppm. Further research on nanoparticles is needed to determine both the economical doses of TiO2NP pre-application and its uptake by the plant.
Keywords: Endüstri Bitkileri; Seed; Germination index; Industrial Crops; Bahçe Bitkileri; Titanium dioxide nanoparticles; Germination percentage; Germination index; Germination percentage; Safflower; Seed; Titanium dioxide nanoparticles; Safflower